2014
DOI: 10.1042/bj20131288
|View full text |Cite
|
Sign up to set email alerts
|

The ability of TRIM3 to induce growth arrest depends on RING-dependent E3 ligase activity

Abstract: Mutation of the TRIM (tripartite motif)-NHL family members brat and mei-P26 perturb the differentiation of transit-amplifying progenitor cells resulting in tumour-like phenotypes. The NHL (named after the NCL1, HT2A and LIN41 repeat) domain is essential for their growth suppressive activity, and they can induce cell-cycle exit in a RING-independent manner. TRIM3 is the only bona fide tumour suppressor in the mammalian TRIM-NHL subfamily and similar to the other members of this family, its ability to inhibit ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 66 publications
1
33
4
Order By: Relevance
“…Our molecular study revealed that TRIM3 could suppress P53 signaling, facilitate cell growth and resistance to cisplatin-induced cell apoptosis. Our finding indicates TRIM3 plays a oncogenic role in P53 WT breast cancer cells, which is opposite to previous studies [19,31]. This interesting finding not only increases the understanding of P53 post-translational modifications but also implicates the multiface of TRIM3 in different cancer background.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Our molecular study revealed that TRIM3 could suppress P53 signaling, facilitate cell growth and resistance to cisplatin-induced cell apoptosis. Our finding indicates TRIM3 plays a oncogenic role in P53 WT breast cancer cells, which is opposite to previous studies [19,31]. This interesting finding not only increases the understanding of P53 post-translational modifications but also implicates the multiface of TRIM3 in different cancer background.…”
Section: Discussioncontrasting
confidence: 97%
“…TRIM3 belongs to the group of tripartite motif family and is composed of zinc-binding domain, RING domain, B1/2 domain and coiled region [31]. TIRM3 was firstly reported as the partner of myosin and facilitate the transportation of the target proteins [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM3 functions as a tumor suppressor (1013). Studies of cancer cells have also shown that TRIM3 overexpression can inhibit cell proliferation (13,14). The present results of CCK-8 and western blot (PCNA and cyclin D1) analyses in RA FLS were in accordance with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that TRIM3 is a candidate tumor suppressor gene for glioblastomas (1012) and colorectal cancer (13). Overexpression of TRIM3 inhibited cell proliferation of cancer cells (13,14). However, little is known about the expression and function of TRIM proteins, including TRIM3 in RA progression.…”
Section: Introductionmentioning
confidence: 99%